PENGARUH MOTIVASI DAN KOMPETENSI TENAGA KESEHATAN TERHADAP KINERJA PUSAT KESEHATAN MASYARAKAT DALAM PELAYANAN KESEHATAN DI KOTA PALU SULAWESI TENGAH - Muh. Nawawi (Indonesian Journal of Dialectics, 2011)
The study to indicate a phenomenon of the low performance of public health centers in health services in Palu, Central Sulawesi. The formulation of research problem is how much influence the motivation and competency of health personnel to the performance of community health centers in health services in Palu, Central Sulawesi.The used of theory is motivation theory of Frederick Herzberg (two factor theory), the competency theory of Spencer and Spencer (five types of competency characteristics), and performance theory of Poister (seven dimensions of organizational performance for public and nonprofit organizations).This study was designed quantitatively, with explanatory survey method. The sampling technique used is proportional stratified sampling. Secondary data collection through the documentation study. While the primary data through questionnaires, interviews (confirmation of the data collected through questionnaires) and observation. Analysis of the data used is the analysis of Structural Equation Modeling.The results of this research showed the motivation of health personnel influence positive and strong, while the competency of health personnel influence positive and enough on the performance of community health centers in health services in Palu. These results indicate a difference from the theoretical concept, in which competency should have more influence than with motivation. Competency is the basic for the success of a performance, while motivation is basically acting as the driving factor for a person to improve performance. Thus, the proposed new concept is "In health activities, the influence of motivation on the performance of health personnel is stronger than the competency of the employees themselves."